2018
DOI: 10.1007/s12098-018-2649-5
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity Assessment by the Modified Shuttle Walk Test and its Correlation with Biochemical Parameters in Obese Children and Adolescents

Abstract: Obese children and adolescents have reduced exercise capacity when compared to normal individuals. The MSWT performance seems to have a negative association with BMI, but is not correlated with blood biochemical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A previous study from our group (de Assumpção et al, 2018) showed a negative correlation between nutritional status and MST distance in obese children and adolescents with no respiratory disease. Increased nutritional status leads to an extra body demand to be transferred during daily tasks and to the tendency of subjects to become even more inactive (Bovet et al, 2007; Castro-Piñero et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
“…A previous study from our group (de Assumpção et al, 2018) showed a negative correlation between nutritional status and MST distance in obese children and adolescents with no respiratory disease. Increased nutritional status leads to an extra body demand to be transferred during daily tasks and to the tendency of subjects to become even more inactive (Bovet et al, 2007; Castro-Piñero et al, 2011).…”
Section: Discussionmentioning
confidence: 58%
“…The use of MST to assess the functional capacity in children with chronic diseases or in healthy conditions is already well established in literature 9 . Previous studies described different reference equations to predict the walking distance or the VO 2 peak of children and adolescents during the MST, as well as of patients with cystic fibrosis 10 , asthma 11 , and adolescents with obesity 12 .…”
Section: Introductionmentioning
confidence: 99%